Efficiency of agroecological practices in cacao production in Ucayali, Peru - Orjuela Ramirez, Guillermo; López-Estrada, Sebastian (2024)
Despite the overall growth of cacao cultivation in Ucayali, Peru's third largest cacao-producing region, it has experienced a production decline associated to high temperatures, low rainfall, and significant pest and disease outbreaks, which negatively impact their efficiency. To face these challenges and maintain production levels, farmers use diverse agroecological practices. However, are agroecological practices efficient?